Analisis Penerapan Fintech Terhadap Kinerja Keuangan Bank di Provinsi Bali : Studi Kasus pada Bank BPD Bali, Denpasar - Ni Wayan Rumadiasih; Ni Made Yusmini; Pande Putu Ida Yuliantari (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
This study aims to assess the positive impact of financial technology (mobile banking, internet banking, and SMS banking) on ROA, ROE, and NIM at Bank BPD Denpasar. The research employs quantitative methods, utilizing secondary data from the annual financial reports of Bank BPD Bali, Denpasar, for 2021-2024, along with national and international journals and official websites. From a population of 36, purposive sampling was used to select 12 samples. The findings indicate that there are significant differences in ROA, ROE, and NIM before and after the adoption of Fintech, with significance levels of 0.025, 0.000, and 0.038 respectively, all of which are below the 0.05 threshold. These results demonstrate that the integration of financial technology has led to a notable increase in ROA, ROE, and NIM, indicating an overall improvement in the bank's financial performance. The study concludes that the adoption of Fintech positively influences the financial metrics of Bank BPD Denpasar, suggesting that such technology can enhance banking performance.